Quality Management Practices and Their Influence on Academics’ Innovative Work Behavior and Performance in Nepalese Higher Education Institutions - Adhikari, Hrizu; Kaur, Kamaljeet (Journal of Advanced Academic Research, 2026)
The paper examines the association of Quality Management Practices (QMP), Innovative Work Behavior (IWB) and Academic Performance (AP) among scholars in Nepalese Higher Education Institutions (HEIs). The growing needs of most HEIs in Nepal pertaining to accreditation, competition, and academic excellence has made it important to comprehend the effects of institutional quality practices on faculty behavior and performance. The study follows a quantitative research design with qualitative information as it is guided by the perspectives of quality management and organizational behavior. The structured questionnaires and stratified random sampling were used to collect primary data out of 200 full-time and part-time academics. QMP, IWB and AP were measured using validated perceptual scales. Analysis of data has been done by means of SPSS and Jamovi, with inclusion of descriptive statistics, reliability and validity analysis, correlation test and mediation analysis using regression. The results show that Quality Management Practices relate positively and significantly with the Innovative Work Behavior (β= 0.59, p < .001) and Academic Performance (β= 0.53, p < .001). Academic Performance (0.44, p < .001) is also positively correlated with the Innovative Work Behavior (meaning that it mediates the relationship between QMP and performance outcomes), which proves to be their relationship. The qualitative interview data also emphasizes the leadership commitment as one of the main drivers of innovation and the engagement of stakeholders and the practice of continuous improvement as the factor that helps to achieve better teaching effectiveness and engagement with the institution. The research provides the empirical findings to justify the role of quality management as a strategic tool to facilitate innovation and academic performance in Nepalese HEIs.